Epidemiology and Risk Factors of Melanoma: A Review - Claudio Conforti; Iris Zalaudek (Mattioli1885, 2021)
We are currently witnessing a worldwide increase in the incidence of melanoma. Incidence in Europe is about 25 cases per 100,000 population, while in Australia it reaches a rate of 60 new cases per 100,000. While the epidemiological curves of the 1980's and 1990's suggested an increase in the incidence of melanoma across all age groups, the last 10 years' data indicates a 5% reduction in the incidence of thin melanoma in young individuals aged between 15 and 24. This suggests a positive impact of primary prevention campaigns [1-2]. The risk factors associated with melanoma are different and multifactorial: on one hand, there is a genetic predisposition, as evidenced by the increased risk in patients with dysplastic nevus syndrome, with familial melanoma or familial melanoma syndromes; on the other hand, the unprotected interaction between UV rays and phototypes I-II increases the risk of developing melanoma, especially in case of sunburns in pediatric age. This review aims to summarize melanoma epidemiology and risk factors.